PHYLOGENY AND CLASSIFICATION OF THE IRIDACEAE AND THE RELATIONSHIPS OF IRIS - GOLDBLATT, P. (Annali di Botanica, 2000)
Iridaceae are a well defined family of some 1800 species and between 60 and 70 genera. Molecular studies of chloroplast DNA has confirmed the position of the family in the order Asparagales, contrary to earlier work that placed the Iridaceae in Liliales. The family comprises two large assemblages of species, currently regarded as subfamilies Ixioideae and Iridaceae. The relationships of the remaining seven genera, included in subfamilies Isophysidoideae and Nivenioideae, have been rendered uncertain because of the lack of congruence between molecular and morphological studies using different outgroups and/or different data sets. Ixioideae, the largest subfamily, comprises more than half the total species in the family. Largely African, with fair representation in Eurasia, the generic phylogeny of Ixioideae is poorly understood. Most genera exhibit a considerable range of floral diversity based on floral zygomorphy and the elaboration or reduction of the perianth tube. Production of floral nectar and pollination by long-tongued insects including anthophorine bees, Lepidoptera, longproboscid flies and birds is a recurring theme but reversals to actinomorphy, often accompanied by the suppression of nectar production, has occurred in species of several genera that are pollinated by hopliine beetles. Virtually worldwide in distribution, Iridoideae comprise five tribes, the Australian Diplarrheneae, the Australasian and American Sisyrinchieae, the exclusively American Trimezieae (= Mariceae) and Tigridieae, and the Old World Irideae. Iris and Moraea constitute the major genera of this last tribe, Iris a North Temperate genus and Moraea largely sub-Saharan African. Several small genera allied to Iris or Moraea are believed to have flowers modified for different pollination strategies and have been shown by molecular data to be nested with one or other of the larger genera. Vegetative diversity, especially in the leaf and rootstock, is an important variable in Iris whereas floral divergence and vegetative uniformity characterize Moraea. Genera of Irideae appear to be primarily adapted for pollination by bees foraging for nectar and pollen transfer is passive. Specialization has shifted the pollination strategy either to a generalist system using flies, bees and beetles, or a specialist system using bees foraging for pollen, or carrion flies attracted to foul odors, or hopliine beetles that use flowers as sites for assembly and mating.